The status of Plumularia lagenifera Allman, 1885 (Cnidaria, Hydrozoa) and related species - Schuchert, Peter (Zootaxa, 2013)
The current status of Plumularia lagenifera Allman, 1885, a common thecate hydroid of the west coast of the USA and Canada, is problematic as it is difficult to distinguish from the near cosmopolitan and very variable Plumularia setacea. Type material of P. lagenifera and newly collected material of P. lagenifera and P. setacea from the region of the type locality of the former was used to compare it to P. setacea from the Atlantic. Measurements of a number of morphological traits were made and analysed using principal components analyses. Type material of the Californian Plumularia palmeri Nutting, 1900 was also included in the comparisons and confirmed the view of earlier workers that it is indistinguishable from P. setacea. Additionally, South African material referred to P. lagenifera by Millard (1975) was compared to the ma-terial from the NE Pacific. Plumularia lagenifera remains difficult to separate from P. setacea. The convex outer wall of the hydrotheca offers the only operational character to distinguish P. lagenifera from P. setacea, which always has straight or even concave hydrothecae. For morphological and biogeographic reasons, South African P. lagenifera sensu Millard (1975) should be referred to P. gaimardi (Lamouroux, 1924).